2010
DOI: 10.1289/ehp.0901159
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Lung Disease in World Trade Center Responders Exposed to Dust and Smoke: Carbon Nanotubes Found in the Lungs of World Trade Center Patients and Dust Samples

Abstract: ContextAfter the collapse of the World Trade Center (WTC) on 11 September 2001, a dense cloud of dust containing high levels of airborne pollutants covered Manhattan and parts of Brooklyn, New York. Between 60,000 and 70,000 responders were exposed. Many reported adverse health effects.Case presentationIn this report we describe clinical, pathologic, and mineralogic findings in seven previously healthy responders who were exposed to WTC dust on either 11 September or 12 September 2001, who developed severe res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 33 publications
2
84
0
3
Order By: Relevance
“…29 One air sample and two blanks were also analyzed by NIOSH Method 7402 via TEM to determine the percentage of asbestos fibers among the fibers counted by PCM. 30 An air sample collected from within was tested as described above by EPA AHERA method. 24 …”
Section: Air Testingmentioning
confidence: 99%
“…29 One air sample and two blanks were also analyzed by NIOSH Method 7402 via TEM to determine the percentage of asbestos fibers among the fibers counted by PCM. 30 An air sample collected from within was tested as described above by EPA AHERA method. 24 …”
Section: Air Testingmentioning
confidence: 99%
“…30 Data published by Murr and co-workers 31,32 identified MWCNTs and carbonaceous nanoparticles in methane or propane flames generated by kitchen stoves and from fuel-gas combustions. Notably, Wu et al 33 reported that CNTs have been found in lung tissues from subjects exposed to dusts and smoke during the 11 September 2001 collapse of the World Trade Center in New York. Muller and Nowack 34 calculated the predicted environmental concentration for CNTs in the air and they estimated a value between 0.0015 g / m 3 ͑defined as "realistic exposure"͒ and 0.0023 g / m 3 ͑high exposure͒.…”
Section: Environmental Exposure To Cntsmentioning
confidence: 99%
“…Findings of persistent large particles in sputum, bronchoalveolar lavage, and lung biopsies suggest overload of normal defense mechanisms (32)(33)(34)(35).…”
Section: Special Article What We Have Learned About Health Effectsmentioning
confidence: 99%